Contextual Effect of Preschool on the Development of Children Under Five in Surabaya, East Java - Ajeng Ayu Titah Pujangkara; Harsono Salimo; Eti Poncorini Pamungkasari (Journal of Maternal and Child Health, 2020)
Background:The development of children in the first 1000 days is influential in the long term. Therefore, it requires education at an early age to achieve optimal development. This study aimed to analyze the contextual effect of early childhood education on the development of children under five at Surabaya.Subjects and Method:This was a cross-sectional study conducted 25 preschools in Wonokromo, Surabaya, East Java, Indonesia. The study population was all children aged 2-5 years. A sample of 200 children aged 2-5 years from 25 preschools was selected randomly. The dependent variable was child development. The independent variables were the history of infectious disease, exclusive breastfeeding, number of children, maternal education, maternal occupation, family income, nutritional status, mother tongue, birth weight, and preschool level. The data were analyzed using a multilevel multiple logistic regression run on STATA 13.Results: